The effect of cooking process on antioxidant activities and total phenolic compounds of five colored beans - Chutipanyaporn, Priyanuch; Kruawan, Kalyarat; Chupeerach, Chaowanee; Santivarangkna, Chalat; Suttisansanee, Uthaiwan (Food and Applied Bioscience Journal, 2017)
Beans are sources of many nutrients including proteins, carbohydrate, minerals, vitamins, dietary fiber and other bioactive compounds with protective and therapeutic effects towards oxidative stress and cell damage related diseases. Although many previous researches have been focused on antioxidant properties of beans, limited information on the comparison of five colored beans under cooking process regarding their antioxidant properties and total phenolic compounds (TPC) is currently available. Thus, the aim of this study was to investigate the effect of cooking process on antioxidant activities and TPC of five colored beans including mungbean, black bean, red kidney bean, white bean and soybean. Raw and beans cooked in boiling water for 20 min were freeze-dried and ground using a grinder. All samples were extracted with 70% (v/v) aqueous ethanol for 2 hours at 30°C. The antioxidant activities were analyzed using 1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging assay, and TPC was determined using Folin–Ciocalteu reagent. As results, the antioxidant activities and TPC of all five colored beans were elevated after the cooking process (DPPH values of 200-800 μmole TE/100 g dry weight and 400-1500 μmole TE/100 g dry weight of raw and cooked samples, respectively, and TPC values of 40-300 mg GAE/100 g dry weight and 80-300 mg GAE/100 g dry weight of raw and cooked samples, respectively). Black bean exhibited the highest TPC and DPPH scavenging activities, followed by red kidney bean, mung bean, soy bean and white bean, respectively. The high antioxidant activities and TPC in black bean might be due to the content of extracted bioactive compounds such as flavonol glycosides, anthocyanins and tannins. In addition, heat treatment greatly affected antioxidant activity and TPC of beans. This is possibly because of the disruption of plant cell walls during cooking, and sequentially, more bioactive compounds are released from the plant cells.